2017
DOI: 10.4055/cios.2017.9.2.232
|View full text |Cite
|
Sign up to set email alerts
|

Revision Surgery for Recurrent Pain after Excision of the Accessory Navicular and Relocation of the Tibialis Posterior Tendon

Abstract: BackgroundThe results of operative treatments for symptomatic accessory navicular are debatable. In some cases, recurrent pain may develop after the Kidner procedure. The purpose of this study is to review the reasons for recurrent pain after the Kidner procedure and to suggest possible options for revision surgery.MethodsWe reviewed the clinical and radiological outcomes in 9 patients who underwent revision surgery for recurrent pain after the Kidner procedure. During the revision surgery, the tibialis poster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…In the literature, only 1 clinical study investigated recurrent pain after the Kidner procedure. In a study of 9 revision cases after a primary Kidner procedure, Choi and Lee 5 observed 7 patients (78%) demonstrating a planovalgus deformity. In our study, only 11 patients (52%) had a planovalgus deformity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the literature, only 1 clinical study investigated recurrent pain after the Kidner procedure. In a study of 9 revision cases after a primary Kidner procedure, Choi and Lee 5 observed 7 patients (78%) demonstrating a planovalgus deformity. In our study, only 11 patients (52%) had a planovalgus deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its relatively successful outcomes, pain after the Kidner procedure has been reported from several studies. 5,31,33 However, the etiology of these symptoms and its surgical management have not been clearly determined. Vaughan and Singh 33 reviewed 6 studies on the outcomes of the Kidner procedure and found that 80 of 124 (65%) feet that had preoperative flatfoot deformity still had postoperative flatfoot deformity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the ANB patients experience persistent pain even after the surgery, which reflects the necessity for more accurate risk stratification of ANB. [11]…”
Section: Introductionmentioning
confidence: 99%